Faktor-Faktor Yang Berhubungan dengan Kejadian Diare pada Anak Umur 0 – 24 Bulan - Putri Aulia Arza; Rini Sri Wahyuni (Jurnal Gizi, 2018)
Mothers’ knowledge, attitude, breasfeeding behaviour and complementary feeding practices  are important to minimize the effects of morbidity and mortality associated with diarrhea diseases. This study aims to determine the factors associated with the incidence of diarrhea inchildren aged 0-24 months.  The research is quantitative analytic survey through cross sectional approach.The total number of respondents were 60 respondents through purposive sampling technique.Analysis of data in this study using chi-square statistic.  This research result indicates that mother’s knowledge (p-value = 0,15) and attitude (pvalue = 0,49) are not relationship with the occurrence of diarrhea. However, breastfeeding behavior (p-value = 0,004) and Complementary feeding practices  (P-value = 0,00) are associationsignificantly with diarrea in children aged 0-24 months who hospitalized at Islamic hospital "Ibnu Sina" Yarsi in Payakumbuh.  It is expected that mothers with children under five to pay attention to the give the best and healthy behavior of  breastfeeding and Complementary feeding practices  so that children not suffer some disease especially diarrhea.  Keyword: mother’s knowledge, mother’s attitude, breastfeeding behavior, complementary feeding practices, diarrhea